A Cultural Content Analysis in English Textbook “English on Target” for SMA/MA Grade X - Nur Amalina Masturah; Muh .Asrori; Hefy Sulistyawati (Universitas Sebelas Maret, 2021)
This study was conducted to find out the representation of cultural content in English language textbook. The object of the research was an English textbook “English on Target” for SMA/MA grade X. The method used by this research was descriptive content analysis. Some underlying models proposed by Moran (2001) and Cortazzi and Jin (1999) were used as the main framework to analyze the textbook. The data were collected from all texts in reading exercises of the textbook. The analysis revealed two main facts. Firstly, dimension of product is dominant in the textbook followed by practices, persons, perspectives and communities. Secondly, most of those types of culture are presented in target culture followed by source culture, culture-free, and international culture. The result showed that the representation of culture indicated that there were some elements of cultural content lack of presentation in the textbook.